The Impact Of Work Communication And Discipline On Employee Performance - Ade Risna Sari; Geofakta Razali; Darmawati Manda; Arief Yanto Rukmana; Pitono Pitono (Transformasi: Journal of Economics and Business Management, 2023)
The objective of this study is to determine and analyze the effects of the work environment, communication, and discipline on employee performance. The background of this study is the phenomenon of inadequate company facilities, budget constraints, poor communication with colleagues, where employees tend to form separate groups, and the low level of discipline and self-awareness of employees and superiors regarding compliance with regulations. The study is quantitative, and the data was analyzed using multiple linear regression. A sample of 41 employees was taken with the saturated sampling approach. The results showed that work facilities had a good and statistically significant effect on staff performance at PT. Prosperous Administration Development, as well as on work communication and work discipline. Furthermore, the impact of work facilities, communication, and discipline on the performance of PT. Bina Administration Sejahtera staff was also significant.